Electrochemical faceting of metal electrodes - Arvia, Alejandro Jorge (1986)
Electrochemical faceting is a term recently coined to denote the preferred crystallographic orientation of grains in polycrystalline metals developed when they are subjected to periodic potential perturbations of determined characteristics. Electrochemical faceting can also be applied to small single crystal beads resulting from melting polycrystalline metal wires. By properly adjusting the conditions defining the periodic perturbation, the resulting electrode surface acquires different preferred orientations which, depending on the nature of the electrode metal, can be followed either electrochemically through conventional voltammetry in the H and O electroadsorption/electrodesorption potential range, and in upd of different metals, or by scanning electron microscopy. The procedure has already been successfully applied to platinum, gold, rhodium and palladium. Electrochemical faceting involves at least two stages, namely, the initiation stage related to an electroadsorption process and a propagation stage associated with the electrodissolution and electrodeposition of the base metal in the acid electrolyte. Stabilization procedures for the freshly oriented surfaces and roughness development are also considered.